Steering human evolution - Dror, Yehezkel, 1928- author.
1 online resource (viii, 197 pages)
Keywords: "Humanity must steer its evolution. As human knowledge moves a step ahead of Darwin's theories, the book presents the emergence of human-made metaevolution shaping our alternative futures. This novel process poses fateful challenges to humanity, which require regulation of emerging science and technology which may endanger the future of our species. However to do so successfully, a novel 'humanity-craft' has to be developed; main ideologies and institutions need redesign; national sovereignty has to be limited; a decisive global regime becomes essential; some revaluation of widely accepted norms becomes essential; and a novel type of political leaders, based on merit in addition of public support, is urgently needed. Taking into account the strength of nationalism and vested interests, it may well be that only catastrophes will teach humanity to metamorphose into a novel epoch without too high transition costs. But initial steps, such as United Nation reforms, are urgent in order to contain calamities and may soon become feasible. Being both interdisciplinary and based on personal experience of the author, this book adds up to a novel paradigm on steering human evolution. It will be of great interest to scholars and researchers of modern history, evolution sciences, future studies, political sciences, philosophy of action, and science, and technology. It will also be of wide appeal to the general reader anxious about the future of life on earth"--